Mucin 1 Gene (MUC1) and Gastric-Cancer Susceptibility - Saeki, Norihisa (Molecular Diversity Preservation International (MDPI), 2014)
Gastric cancer (GC) is one of the major malignant diseases worldwide, especially in Asia. It is classified into intestinal and diffuse types. While the intestinal-type GC (IGC) is almost certainly caused by Helicobacter pylori (HP) infection, its role in the diffuse-type GC (DGC) appears limited. Recently, genome-wide association studies (GWAS) on Japanese and Chinese populations identified chromosome 1q22 as a GC susceptibility locus which harbors mucin 1 gene (MUC1) encoding a cell membrane-bound mucin protein. MUC1 has been known as an oncogene with an anti-apoptotic function in cancer cells; however, in normal gastric mucosa, it is anticipated that the mucin 1 protein has a role in protecting gastric epithelial cells from a variety of external insults which cause inflammation and carcinogenesis. HP infection is the most definite insult leading to GC, and a protective function of mucin 1 protein has been suggested by studies on Muc1 knocked-out mice.